Biodegradable Polymeric Nano-composites for Microbial Growth Control and Wound Healing - Pandey, Vivek Kumar (IIT (BHU), Varanasi, 2020)
Nanomaterials are already being used in numerous household products as well as in several industrial applications due to their unique properties. The biomedical, pharmaceutical, and food packaging industries worldwide are showing great interest in fabricating and developing nanomaterials based products to address the problems associated with biodegradability, eco-friendly nature and efficacy of various products currently being used.
This Thesis Submitted by IIT(BHU), Varanasi. PhD Scholar and Supervised by - Pradeep kumar Mishra
Keywords: Biodegradable; Polymeric; Microbial Growth; Wound Healing